#TITLE_ALTERNATIVE# - ALVIORI (NIM : 10212080), ADITYA
As one of development country in the world, Indonesia need much electrical energy. The electrical energy used by various sectors. The biggest electrical energy consumption based PT.PLN are household and industry. The energy efficiency had did by government, but the efficiency not succeeded. The reason is the energy consumer is not involved in efficiency. With electronic disaggregation, the energy consumer will more involve in efficieny than before. The information, like Cost Structure, from disaggregation process can used by energy consumer to increase their involvement en energy efficiency. In this research, the principle of disaggregation are event-based and low-sampling frequency. The disaggregation algorithm placed in cloud server. KWH-Meter send power data to cloud server via MQTT protocol. That data used by disaggregation algorithm for the energy analyze. The disaggregation algorithm tested by 5 different power bulbs lamp where ON and OFF state applied randomly to bulbs. The algorithm will detect the state of each lamp, average power of each lamp, and energy consumption of each lamp in percentage. The experiment results is the disaggregation algorithm detected all of state of bulbs and succeeded to determine average power and energy consumption of each lamp. The algorithm also succeeded to send experiment results to Android Apps with MQTT protocol.